Non-canonical amino acids bearing thiophene and bithiophene: synthesis by an Ugi multicomponent reaction and studies on ion recognition ability - Esteves, Cátia Isabel Canavezes (2017)
Novel thienyl and bithienyl amino acids with different substituents were obtained by a multicomponent Ugi reaction between a heterocyclic aldehyde, an amine, an acid and an isocyanide. Due to the presence of the sulphur heterocycle at the side chain, these unnatural amino acids are highly emissive and bear extra electron donating atoms so they were tested for their ability to act as fluorescent probes and chemosensors in the recognition of biomedically relevant ions in acetonitrile and acetonitrile/water solutions. The results obtained from spectrophotometric/spectrofluorimetric titrations in the presence of organic and inorganic anions, and alkaline; alkaline-earth and transition metal cations indicated that the bithienyl amino acid bearing a methoxy group is a selective colorimetric chemosensor for Cu2+, while the other (bi)thienyl amino acids act as fluorimetric chemosensors with high sensitivity towards Fe3+ and Cu2+ in a metal-ligand complex with 1:2 stoichiometry. The photophysical and ion sensing properties of these amino acids confirm their potential as fluorescent probes suitable for incorporation into peptidic frameworks with chemosensory ability.